Implementasi Evaluasi Lahan untuk Pengembangan Komoditas Tanaman berdasarkan Kesesuaian Agroklimat - Mujiyo Mujiyo; Rahayu Rahayu; Novi Rahmawati Sutopo (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2020)
Research activity is a form of expert service by the Research Group (RG) of "Agricultural Development Based on Local Soil-Land Characteristics" to its partner of the Wonoagung Wonogiri Organic Agriculture Association (Perkumpulan Pertanian Organik Wonoagung Wonogiri, PPOWW). The provision of suitable land for plant growth by partner is a required aspect in the development of certain commodities. Expert services by the RG is involving the implementation of land suitability evaluation based on agroclimatic conditions. The objective of the activity is to provide data and information on land suitability levels for certain commodities based on climatic conditions. The area which became the object of this research activity is where the PPOWW partner is located; namely Sidoharjo Sub-district, Wonogiri Regency. The secondary data was obtained from relevant sources in the form of annual rainfall (mm year-1), annual average air temperature (°C) and annual average humidity (%). The method of agroclimate suitability evaluation was carried out by following the procedure from Food and Agriculture Organization (FAO), by matching climatic conditions with plant growth requirements. Plant commodities that were evaluated for their suitability were durian, salak, mangosteen, apples and avocado. The results showed that durian is a suitable commodity (S1) with climatic conditions in Sidoharjo Sub-district. Salak and avocado are quite suitable commodities (S2). Meanwhile, mangosteen is a commodity which is moderately suitable (S3); whereas apple is a commodity that is not suitable (N). Durian, salak and avocado are commodities which have the potential to be developed by PPOWW in Sidoharjo Sub-district. The next stage of the evaluation implementation requires data and information on the suitability of soil conditions.